TS-1 loaded with sulfated zirconia as bifunctional oxidative and acidic catalyst for transformation of 1-octene to 1,2-octanediol - Prasetyoko, Didik; Ramli, Zainab; Endud, Salasiah; Nur, Hadi (Elsevier, 2005)
Titanium silicalite (TS-1) loaded with sulfated zirconia as bifunctional oxidative and acidic catalyst has been synthesized at various loadings of zirconium (2–20 wt%). Structure and properties of the samples were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR), Fourier transform infrared (FTIR) and UV–vis diffuse reflectance (UV–vis DR) spectroscopy techniques. The monolayer dispersion capacity of zirconium on the TS-1 was found to be 0.65 Zr4+ nm−2 TS-1. The UV–vis DR spectroscopy showed that the tetrahedral coordination of the titanium was observed in all samples, while octahedral zirconium was only observed in the samples containing high amount of zirconium loading (10, 15 and 20 wt%). The TPR profiles suggested that the zirconium structure impregnated on the surface of TS-1 with high amount of zirconium loading (15 and 20 wt%) have a similar structure to sulfated zirconia calcined at 500◦C. Adsorption of pyridine onto the samples indicated that Bronsted acid sites are only present in samples with high sulfated zirconia loading, i.e. 15 and 20 wt%. As analyzed by XRD, the formation of Bronsted acid sites is due to the presence of disulfate species on the surface of TS-1. It has been demonstrated that samples with 15 and 20 wt% loadings of sulfated zirconia showed activity towards consecutive transformation of 1-octene to 1,2-octanediol through the formation of 1,2-epoxyoctane using aqueous hydrogen peroxide.